Exploring midwifery students' experiences of professional identity development during clinical placement: A qualitative study. (August 2022) - Sun, Jingxian; Wang, Aihong; Xu, Qingqing
Abstract: Background: Healthy China 2030 has proposed to strengthen the investment in midwifery education to prepare more qualified midwives to address the shortage of midwifery workforce in China. The formation of a strong professional identity has been demonstrated to be a vital enabler for successfully transitioning from university to work. As midwifery is a practice-based profession, clinical placement is a key period for midwifery students' professional identity development, where they can be part of the profession and exposed to professional behaviour and interaction in the real world. However, it has not yet been explored in terms of the professional identity development of midwifery students in China during clinical placement. Aim: To gain insight into the professional identity development experiences of midwifery students in China during clinical placement. Design: A qualitative study using a descriptive phenomenological approach. Methods: Semi-structured interviews were conducted with fourteen final-year midwifery students who were undertaking clinical placement in four public hospitals in central China between March 2021 and May 2021. The transcribed data were analyzed following the Colaizzi's phenomenological analysis method. Results: A total of one category, two theme clusters and seven themes emerged. The overarching category "conflicting experiences of professional identity development" was identified from the interaction of two theme clusters, "positive experiences motivating professional identity development" and "negative experiences impeding professional identity development". Four themes including "feeling the sense of accomplishment for facilitating smooth births", "developing professional competence", "positive role models of clinical mentors", and "cooperative inter-professional relationships" fell into the theme cluster of "positive experiences motivating professional identity development"; while the other three themes including "high-intensity working state", "emotional instability of birthing women", and "feeling insufficient in professional competence" fell into the theme cluster of "negative experiences impeding professional identity development". Conclusions: The conflicting experiences of professional identity development among midwifery students might lead to the emergence of confusion and further decrease their retention intention in the profession. Thus, intervention strategies should be adopted to promote midwifery students' professional identity development during clinical placement, so as to prepare confident and motivated midwives to provide high-quality maternal care and address the shortage of midwifery workforce in China.